Students’ perceptions on MOOCs among public universities in Malaysia / Mohammad Nasir Abdullah ... [et al.] - Abdullah, Mohammad Nasir; Abdul Rahim, Ain Nazierah; Ahmad Zaki, Ahmad Hafiy; Azizan, Ayu Najihah; Jamaldin, Noor Shuhada; Azizi, Luqman Al Hakim; Jamaludin, Nabilah Atiqa (Universiti Teknologi MARA, Perak, 2019)
Massive Open Online Courses (MOOCs) are open online courses that use information technologies to attract people in experience learning using Internet. MOOCs is the platform that students will able to obtain more knowledge and thus lead to increasing of the expectation of learning outcomes. This study aims to determine the relationship between learning strategies, cognitive appraisal and difference between the genders of students on future intended to use MOOCs among public universities in Malaysia. The study was conducted among 126 students’ public universities in Malaysia that involve in MOOCs. This study revealed that there is no significant difference between male and female on the intention of using MOOCs. Besides, two variables in learning strategies that is deep learner and surface learner are significant towards future intended used of MOOCs. The results also showed that threat and challenge have no association between future intended used of MOOCs. In conclusion, we found that students with deep learner attitude and surface learner attitude were the most importance factors that contribute to future intended to use MOOCs and these factors are work in silo.